Educational testing and measurement : classroom application and practice - Kubiszyn, Tom; Borich, Gary D. (Hoboken, NJ : John Wiley & Sons, Inc., 2024)
"Education and Testing Measurement, 12th Edition, is an up-to-date, practical resource that will help current and prospective teachers navigate today's ever-changing and complex world of educational testing, assessment, and measurement. This accessible resource equips educators with practical assessment strategies for today's challenges in measuring student progress. It details the global, national, and key statelevel policy changes that drive the ongoing changes in general education and special education testing and assessment practices. The 12th edition presents a balanced perspective of educational testing and assessment, with a unique focus on descriptive statistics and psychometrics (validity, reliability, and fairness). It integrates updated references, readings, and examples to ensure a current look at the field. One of few leading titles to cover Response to Intervention (RTI) support for struggling students, this edition incorporates new thinking including Multi-Tiered System of Support (MTSS), showing how to use continuous improvement and data analysis to improve student outcomes"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Educational tests and measurements -- United States